'The Peanut King' and other pranks: Exploring working culture through apprentice initiations and rituals at the Midland Railway Workshops. - Oliver, Bobbie (2004)
For 90 years,the Western Australian Government Railway (later Westrail)Workshops at Midland were the largest industrial Workshops in Western Australia. From 1998 to 2004, the Workshops was the subject of an extensive history project. Commencing with an oral history programme aimed at interviewing as many past employees as possible, the project has extended (with the aid of grant funds) into an archive of documents and photographs, a collection of tools and other objects, a DVD, a web page and a book of the history of Workshops. Many fascinating aspects of working culture have come to light; this paper focuses on the quaint, and often brutal, rituals to which apprentices were subjected during their first year at the Workshops.Using interviews and written recollections provided by the tradesmen, this paper looks at the substance and the legend of such rituals as the 'Peanut King', and a range of 'pranks' from those designed to be humiliating but harmless to those that threatened and in some cases took lives. The paper will attempt to answer the following questions. To what extent were these rituals a product of the locality, and how much did they retain from a strongly British industrial heritage? Were they aimed at instilling dependability into workmates in an extremely dangerous work place? Did rituals change over time? Where appropriate, comparisons will be made with existing literature on the subject. The paper will include extensive quotations from interviews, so that the voices of the workers may be heard as well as the author's interpretation of their words.